Influência dos níveis de água na dinâmica de macrófitas aquáticas emergentes do banhado do Taim - Rosa, Cristiano Niederauer da (2016)
This work evaluated, throught techniques of Remote Sensing and geoprocessing, the influence of hydrological conditions in the dynamics of emergent aquatic macrophytes in Taim Wetland (TW), important wet area in Rio Grande do Sul. The TW covers about 53% of the entire area of Taim s Ecological Station, a Federal Protected Area, which has its uses shared, mainly between biodiversity protection and irrigation. The irrigation is an important economical activity for the region, however, it changes the hydrological regime of TW, a fundamental feature for the maintenance of local biodiversity. Thus, the understanding of how the hydrological regime impacts TW s biodiversity is an important tool for the management of water resources in the region. In this context, three species of emergent aquatic macrophytes (EAM), Z.bonariensis, S. californicus and S. giganteus, were selected, both considered as biological indicators of TW. In order to evaluate how the water levels impact the three EAM, some analyses on the relationship among the hydrological condition, maps of vegetation occurrence, index for normalized difference (IND) and index of habitat suitability (IHS) were carried out. For the identification of the occurrence areas and determination of IND of EAM, Landsat images from TM and ETM sensors were used, comprising the period between 1984 and 2003, while the IHS and the hydrological regime were obtained from previous studies (Tassi, 2008; Xavier, 2015). The employed methodology showed that the EAM Z.bonariensis and S. californicus are more sensitive to larger water levels (representatives of flood conditions); in this situation, reductions in the occurrence areas of these species were indentified. For smaller water levels (drought conditions), there was an increasing in the occurrence areas of the three species. The IND showed an effective index for the understanding of EAM s response to the hydrological conditions, although in many cases there was so much difficulty in the differentiation of vegetation and water. Generally, good coefficients of determination were found between the IND and the average IHS of three months (month of image + two months previous to the image date), and between the IND and the hydrological condition (water level) of two months previous to the image date. These results are the evidence that the effects of hydrological conditions on the studied EAM are not readily detected, and that anthropic actions can produce long-term effects.